Ethics and Deontology code of the Peruvian College of Physicians: theoretical basis - Ortiz Cabanillas, Pedro (2008)
The theoretical basis for the first two editions of the Deontological Ethics Code of the Peruvian College of Physicians is introduced, in order to show innovations for the last edition. This last version updates the regulations for the deontological tradition of the Peruvian College of Physicans, and systematizes them in three Sections: Ethical Principles of Medicine, Deontological Duties in Medical Practice, and Principles for a Moral Judgement of those who fail to comply the aforementioned principles.